Peran internal audit atas kualitas laporan keuangan pada perusahaan - Eric Fauzi; Dwi Urip Wardono (Jurnal Riset Pendidikan Ekonomi, 2022)
This writing aims to research and determine the role of internal audit on the quality of financial statements in the company. Financial statements are an important part of a company so that they can be taken into consideration in making company decisions. Therefore, the quality of financial reports must be considered because it can affect the decision making of stakeholders. The role of internal audit is highlighted as one that has an important role to improve the quality of financial reports. The sample used in this study is an internal audit who works in a property company. This writing uses a descriptive method, namely, a method that concludes, presents, and analyzes data so as to produce a fairly clear picture of this writing. The results of this study indicate that internal audit plays a role in the quality of the company's financial statements